Antidopaminergic Activity of Vitex negundo (Linn) Roots - Borse, L.B.; Kottai Muthu, A.; Thangatripathi, A.; Borse, S.L. (Asian Journal of Chemistry, 2012)
The objective of the study was to investigate the effect of acetone soluble fraction of methanolic extract of roots of the vitex negundo on dopaminergic function. The effect of acetone soluble fraction of methanolic extract of roots of the Vitex negundo (50 and 100 mg/kg, i.p.) was studied on haloperidol-induced catalepsy in mice, amphetamine induced stereotyped behaviour in rats and dopamine-induced contraction isolated vas deferens preparation of rat. The acetone soluble fraction of methanolic extract of isolated of V. negundo significantly potentiated haloperidol induced catalepsy, antagonized dose dependant amphetamine-induced stereotyped behaviour and also antagonized dopamine induced contractions of rat vas deference. The result suggests that the methanolic extract of Vitex negundo possessed antidopaminergic principle.